Minerals Beneficiation - Mechanism of Intergranular Comminution by Heating - J. H. Brown; A. M. Gaudin (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
In a survey of the effects of heat treatment on the comminution of various rocks, it was found that unusual size distributions often characterize the broken products, and that this is related to a great increase in intergranular fracture1. It is the purpose of the present paper to contribute to an understanding of this effect. In a thesis by one of use, critical consideration was given to many mechanisms which could conceivably be responsible for the increased intergran-ular fracture. It was shown that neither gross chemical changes nor intergranular corrosion are required. Among non-chemical mechanisms the most likely appeared to be (1) Uneven expansion due to thermal gradients, giving spalling (2) In a manner similar to that prevailing in metals, the appearance at high temperature of intergranular weakness. (3) Unequal thermal expansion of adjacent grains. Experiments were designed and conducted to permit a choice among the many alternative mechanisms and in particular among the three listed here. EXPERIMENTAL MATERIALS Tests were made on the materials listed in Table 1. Of each material, only lumps similar in composition and grain size were used. The three marbles listed in Table 1 were analyzed to assure that their chemical compositions did not differ greatly (Table 2). On the basis of the chemical analyses, of differential thermal analyses, and of X-ray powder diffraction patterns, it appeared that the marbles were very similar except for their grain sizes.